Phosphorus Export From Two Contrasting Rural Watersheds in the (Sub) Humid Ethiopian Highlands - Sishu, Feleke K.; Bekele, Ayele M.; Schmitter, Petra; Tilahun, Seifu A.; Steenhuis, Tammo S. (Frontiers in Earth Science, 2021)
Establishing worldwide sustainable and phosphorus efficient cropping systems is urgently needed because the supply of suitable phosphate rock is limited, and excess phosphorus in streams causes eutrophication. One of the impediments in the developing world for sustainable P practices is the lack of studies on the transport and fate of phosphorus. One of these regions with few studies is the Ethiopian Highlands, with permeable volcanic soils. The objective was to establish baseline data on P watershed export in the (sub)humid highlands. Two contrasting watersheds were selected near Lake Tana. For two years, stream discharge and sediment, total P, dissolved P, and bioavailable particulate P concentrations were determined at the watershed outlet. The first watershed is the 57 square kilometer Dangishta, with many lava intrusion dikes, forcing interflow through faults to the surface and preventing the formation of gullies. Interflow was half of the 1.75m annual precipitation, and surface runoff and erosion were minimal. The second watershed was the 9 square kilometer, Robit Bata, with 1.4m precipitation and banks slumping in several river sections. The upper part of the watershed generated saturated excess. A hillslope aquifer in the lower part provided interflow. The average sediment concentrations of 10 g/l in the stream in Robit Bata (11 times that in Dangishta) reflected the sediments from banks slipping in the stream. The hydrology and the soil loss directly affected the phosphorus export. In Dangishta, total particulate P concentration averaged 0.5 mg/l at the outlet. In Robit Bata, the average total particulate P concentration was 2 mg/l. The biologically available particulate P concentration was only twice the concentration in the runoff water. The low phosphorus content of the subsoil slipping in Robit Bata moderated the particulate P at the outlet. Average dissolved P concentrations for both watersheds were around 0.1 mg/l which is in the low range found in temperate climates. It reflects the difference in length of time that phosphorus fertilizers have been applied. Our research concludes that commonly implemented practices such as strengthening river banks and stabilizing gully might not lead to improved water quality in Lake Tana